A Novel Approach to Assess Sleep-Related Rhythmic Movement Disorder in Children Using Automatic 3D Analysis - Gall, Markus; Kohn, Bernhard; Wiesmeyr, Christoph; van Sluijs, Rachel M.; Wilhelm, Elisabeth; Rondei, Quincy; Jäger, Lukas; Achermann, Peter; Landolt, Hans-Peter; Jenni, Oskar G.; Riener, Robert; Garn, Heinrich; et al. (Frontiers in Psychiatry, 2019)
Unlike other episodic sleep disorders in childhood, there are no agreed severity indices for rhythmic movement disorder. While movements can be characterized in detail by polysomnography, in our experience most children inhibit rhythmic movement during polysomnography. Actigraphy and home video allow assessment in the child’s own environment, but both have limitations. Standard actigraphy analysis algorithms fail to differentiate rhythmic movements from other movements. Manual annotation of 2D video is time consuming. We aimed to develop a sensitive, reliable method to detect and quantify rhythmic movements using marker free and automatic 3D video analysis. Patients with rhythmic movement disorder (n=6, 4 male) between age 5 and 14 years (M: 9.0 y, SD: 4.2y) spent three nights in the sleep laboratory as part of a feasibility study (https://clinicaltrials.gov/ct2/show/NCT03528096). 2D and 3D video data recorded during the adaptation and baseline nights were analyzed. One ceiling-mounted camera captured 3D depth images, while another recorded 2D video. We developed algorithms to analyze the characteristics of rhythmic movements and built a classifier to distinguish between rhythmic and non-rhythmic movements based on 3D video data alone. Data from 3D automated analysis were compared to manual 2D video annotations to assess algorithm performance. Novel indices were developed, specifically, the rhythmic movement index, frequency index and duration index to better characterize severity of rhythmic movement disorder in children. Automatic 3D video analysis demonstrated high levels of agreement with the manual approach indicated by a Cohen’s Kappa >0.9 and F1-score >0.9. We also demonstrated how rhythmic movement assessment can be improved using newly introduced indices and according plots for visualization. 3D video technology is widely available and can be readily integrated into sleep laboratory settings. Our automatic 3D video analysis algorithm yields reliable quantitative information about rhythmic movements, reducing the burden of manual scoring. Furthermore, we propose novel rhythmic movement disorder severity indices that offer a means to standardize measurement of this disorder in both clinical and research practice. The significance of the results is limited due to the nature of a feasibility study and its small number of samples. A larger follow-up study is needed to confirm presented results.